Perception and Acceptance of Cesarean Section among Pregnant Women Visiting Antenatal Care Clinic at Tertiary Hospital - Sapkota, Devi Kumari; Gurung, Tak Maya (Journal of College of Medical Sciences-Nepal, 2025)
Background Cesarean section is one of the most performed major surgical procedures for delivering the baby when vaginal delivery is not possible or threats the life of mother or baby or both. Current trends show steady rise in cesarean section rates globally though comparatively lower in developing countries. The objective of the study was to assess the perception and acceptance of cesarean section and to identify the relationship between perception and acceptance of caesarean section among pregnant women. Methods An analytical cross-sectional study carried out among 92 pregnant women visiting Antenatal Care clinic at Bharatpur Hospital, Chitwan Nepal. To assess the perception and acceptance of caesarean section among pregnant women, 5-point Likert scale developed by the researcher and used to collect the required information. Three domain; mode of delivery, mother and baby conditions and expenses for caesarean section included in likert scale to assess the perception. The data was analyzed in Statistical Package for the Social Science (SPSS) version 20 using descriptive and inferential statistics. Results The study findings revealed that of 92 respondents, all of them (100.0%) had good perception towards CS regarding mode of delivery, 98.9% had good perception related to mother’s and baby’s conditions and 98.9% had good perception of CS regarding expenses. Regarding the acceptance of CS, 98.9% agreed to accept CS when medically indicated, whereas 1.1% refused CS under any circumstances. There was a significant relationship between the perception and acceptance for CS (r = 0.304, P-value = 0.03) suggesting that level of perception influences the acceptance of the Caesarean section. Conclusions The result of study indicates that the need of public awareness on preference of natural delivery is important and cesarean section delivery is optional only when the condition contraindicated for natural delivery.